Towards just-in-time (JIT) production system through enhancing part preparation process - Che-Ani, M.N. (IEEE Computer Society, 2018)
In this paper the improvement activity in manufacturing plant has been conducted by focusing outside of production process which is part preparation activity in warehouse area. The Plan-Do-Check-Act (PDCA) cycle has been adopted to identify, analyze, verify and implement the improvement activity with the purpose of creating better management of the part preparation activity. To ensure the successful adaptation of PDCA cycle, a small group consisting of cross-functional team members has been formed to analyze and solve the issue. The ultimate objective is to ensure the process improvement will optimize the efficiency of production systems and achieving the Just-in-Time (JIT) concept. Based on the investigation and implementation of the case study industry, the result shows a successful adaptation of PDCA cycle outside of the production process. The waiting time of the production due to misaligned time of the pre-preparation part had been identified as a root cause and successfully eliminated. Â© 2017 IEEE.